Chemical composition, toxicity and physiological effects of essential oil of Rosemarinus officinalis on lesser mulberry pyralid, Glyphodes pyloalis Walker (Lepidoptera: Pyralidae) - Elham Yazdani; Jalal Jalali Sendi; Alireza Aliakbar (Journal of Crop Protection, 2013)
Mulberry pyralid, Glyphodes pyloalis Walker is an important pest on mulberry. The essential oil of Rosemary Rosemarinus officinalis L. (Lamiales: Lamiaceae) has been investigated on toxicity and physiological characteristics of this moth under controlled conditions. The major compounds of the oil were analyzed as 1, 8 Cineol (20.021%), Borneol (7.17%), Camphor (6.541%), Geraniol (6.281%), Camphene (5.623%), Linalool (4.993%) Alpha fenchyl acetate (4.222%) and Verbenone (4.147%). Lethal and sublethal concentrations (LC10, LC30 and LC50) were estimated 0.77%, 1.18% and 1.59% (v/v) respectively. The essential oil affected the nutritional indices of fourth instar larvae of G. pyloalis. efficiency of conversion of ingested food (ECI), efficiency of conversion of digested food (ECD), relative consumption rate (RCR) and relative growth rate (RGR) were reduced in larvae treated with R. officinalis essential oil while approximate digestibility (AD) in treated larvae was significantly increased compared with the control. The essential oil affected the insect’s some key metabolic compounds like; lipid, protein and carbohydrates. Similarly this effect was also significant in the activities of certain key enzymes like; alpha- amylase, lipase, protease, glutathione-s-transferase and esterases.